2018
DOI: 10.3390/polym10030257
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials Based on Electrospun Chitosan. Relation between Processing Conditions and Mechanical Properties

Abstract: In this paper, it is shown that pure chitosan nanofibers and films were prepared with success in 0.5 M acetic acid as solvent using poly (ethylene oxide) (PEO) at different yields, allowing electrospinning of the blends. After processing, a neutralization step of chitosan followed by water washing is performed, preserving the initial morphology of chitosan materials. The influence of the yield in PEO in the blend on the degree of swelling and hydrophilicity of films and nanofibers is demonstrated. Then, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 32 publications
(44 reference statements)
0
37
0
Order By: Relevance
“…Intensive study of PEO behavior during the electrospinning process has been undertaken due to this fact and because of the excellent biodegradability, biocompatibility, and non-toxicity. These attributes also reflect PEO nanofiber applications in biomedicine and the food industry [7][8][9][10] apart from the above already mentioned improvements in spinnability in combination with chitin or chitosan [11][12][13][14], keratin [15,16], silk [17,18] and other materials.…”
Section: Introductionmentioning
confidence: 92%
“…Intensive study of PEO behavior during the electrospinning process has been undertaken due to this fact and because of the excellent biodegradability, biocompatibility, and non-toxicity. These attributes also reflect PEO nanofiber applications in biomedicine and the food industry [7][8][9][10] apart from the above already mentioned improvements in spinnability in combination with chitin or chitosan [11][12][13][14], keratin [15,16], silk [17,18] and other materials.…”
Section: Introductionmentioning
confidence: 92%
“…Acid formic solvent was selected due to easier feasibility to produce nanofibers by electrospinning compared to acetic acid used previously [ 4 , 5 ]. Whatever the W/FA ratio (mainly over 25/75), electrospinning allows to process chitosan alone, HA/PEO, as well as the chitosan/hyaluronic acid complex.…”
Section: Resultsmentioning
confidence: 99%
“…For determination of the mechanical properties on films after thermal treatment, the complexes and the treated CS were directly stabilized in PBS buffer but for CS before thermal treatment, it was necessary to firstly neutralized CS in alkaline medium before PBS immersion as suggested beforehand [ 4 , 5 ]. From data in Figure 11 , it is concluded that the material is able to be manipulated only when R c ≥ 1.8 corresponding to lower values of swelling and solubility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After electrospinning, nanofibers under protonated form of chitosan are made of chitosan/PEO blends. Pure chitosan nanofibers are recovered by immersion in ethanol/water 70/30 (v/v) containing potassium carbonate (0.2 M) and washing in water [17,18]. An example of the nanofibers obtained is given in figure 4.…”
Section: Applicationsmentioning
confidence: 99%